The spectrochemical determination of certain minor trace elements in plant material - Eve, Desmond John (Rhodes University, Faculty of Science, Department of Chemistry, 1961)
A study has been made of three organic complexing reagents , namely dithizone, oxine and cupferron with a view to developing suitable methods for the separation and concentration of Zn, Co, Ni, Pb, Cu, Mn, Ti , V and Mo prior to the spectrometric determination of their concentrations. In particular the influence of pH on the chloroform extraction of ditihizonates, oxinates and cupferrates from aqueous tartrate and citrate solutions and the separation of iron by oxine extraction has been investigated. The development of a method for the chemical concentration and spectrcgraphic determination of Zn, Co, Ni, Pb, Ti, V and Mo is described and the possibility of determining Nn and Cu flame photometrically as part of the analysis scheme is demonstrated. A specially designed slide rule for the calculation of spectrographic results is described. A direct reading spectrometric method for the determination of Zn, Pb and Cu in plant material is presented. The analysis of plant ash for zinc using the 2138 . 6A spectrum line has been studied and a simple, rapid analysis method is described.
Keywords: Trace elements; Spectrum analysis; Plants -- Analysis; Plants -- Effect of trace elements on; Trace elements in agriculture